2017
DOI: 10.1590/s0100-736x2017001000001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biofilm formation capacity of Pasteurella multocida strains isolated from cases of fowl cholera and swine lungs and its relationship with pathogenicity

Abstract: Pasteurella multocida is a Gram-negative bacillus that causes economic losses due to the development of respiratory diseases in several animal species. Among the mechanisms of virulence, the formation of biofilms is an important factor for bacterial survival in hostile environments. Studies of biofilm formation by P. multocida are needed because P. multocida is an important pathogen involved in respiratory infections. However, in contrast to other microorganisms, few studies of biofilm formation have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(67 reference statements)
2
9
1
Order By: Relevance
“…Of the tested isolates, 36.37%, 27.27%, and 18.18% were SBF, MBF, and WBF, respectively (Figure -2a). The development of bacterial biofilms is presently recognized as one of the most relevant drivers of infections and one of the reasons for treatment failure with antibiotics [76][77][78]. In our present study, 18.18% of study strains were found as NBF (Figure -2a).…”
Section: Resultssupporting
confidence: 48%
“…Of the tested isolates, 36.37%, 27.27%, and 18.18% were SBF, MBF, and WBF, respectively (Figure -2a). The development of bacterial biofilms is presently recognized as one of the most relevant drivers of infections and one of the reasons for treatment failure with antibiotics [76][77][78]. In our present study, 18.18% of study strains were found as NBF (Figure -2a).…”
Section: Resultssupporting
confidence: 48%
“…Most bacteria pathogens of poultry especially E. coli, P. multocida and Staphylococcus gallinarum can be transmitted from one to others including humans in many ways and the most causal agents are excreted from chickens through excreta feces, nasal and oral secretion, and these pathogens can persist in the environmental litters, water, feed, holding and transporting cages, vehicles, clothing of animal attendants (Emery et al, 2017;Goldstone and Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic lysis procedure of QIA amp RNeasy Mini kit (Qiagen, Germany, GmbH) used for RNA extraction according to (Yuan et al 2006). PCR reaction was applied in a Stratagene MX3005P real-time PCR machine where the specific primers (Table 1) for P. aeruginosa; 16s rDNA (housekeeping), pslA (biofilm), lasI (Quorum sensing) according to (Spilker et al 2004;Ghadaksaz et al 2015;Bratu et al 2006) respectively, while for P. multocida kmt1 (housekeeping) and tadG (Biofilm) according to (OIE 2012;de Emery et al 2017) while luxS (Quorum sensing) designed in this study, in brief preparation of PCR mix according to quantitect sybr green PCR kit as the following : 2x QuantiTect SYBR Green PCR Master Mix 12.5μl, Reverse transcriptase 0.25μl, each primers 0. 5μl, RNase Free Water 8.25μl, Template RNA 3μl.…”
Section: Real-time Pcr Screening Of Biofilm and Quorum Sensing Genes Expression After Exposure To Some Essential Oilsmentioning
confidence: 99%